2002
DOI: 10.1128/mcb.22.18.6582-6591.2002
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Rac and Cdc42 Video Imaged by Fluorescent Resonance Energy Transfer-Based Single-Molecule Probes in the Membrane of Living Cells

Abstract: Rho family G proteins, including Rac and Cdc42, regulate a variety of cellular functions such as morphology, motility, and gene expression. We developed fluorescent resonance energy transfer-based probes which monitored the local balance between the activities of guanine nucleotide exchange factors and GTPase-activating proteins for Rac1 and Cdc42 at the membrane. These probes, named Raichu-Rac and Raichu-Cdc42, consisted of a Cdc42-and Rac-binding domain of Pak, Rac1 or Cdc42, a pair of green fluorescent prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
589
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 528 publications
(617 citation statements)
references
References 63 publications
26
589
1
1
Order By: Relevance
“…In vitro analysis of singlecell migration revealed that cell protrusions arise at the front and retract at the back of cells respectively through the localized assembly of the actin controlled by the Rho family of small GTPases ( Fig.1.6.3). At the very tip of the cell front cdc42 GTPase controls actin polymerization, which becomes organized in the parallel bundles and contributes to formation of filopodia and nascent cell-substratum adhesion (Itoh et al, 2002). More backwards, but still at the front Rac1 GTPase regulates actin polymerization, which forms a mesh-like network controlling lamellipodia extension and formation of nascent cell-substratum adhesion.…”
Section: Establishment Of Cell Polaritymentioning
confidence: 99%
“…In vitro analysis of singlecell migration revealed that cell protrusions arise at the front and retract at the back of cells respectively through the localized assembly of the actin controlled by the Rho family of small GTPases ( Fig.1.6.3). At the very tip of the cell front cdc42 GTPase controls actin polymerization, which becomes organized in the parallel bundles and contributes to formation of filopodia and nascent cell-substratum adhesion (Itoh et al, 2002). More backwards, but still at the front Rac1 GTPase regulates actin polymerization, which forms a mesh-like network controlling lamellipodia extension and formation of nascent cell-substratum adhesion.…”
Section: Establishment Of Cell Polaritymentioning
confidence: 99%
“…Polarization-In order to move in a certain direction, a cell first needs to polarize in that direction, i.e., to define its front (that will move forward) and its back (that will remain in the rear and retract as the leading edge protrudes). The central regulators of establishing this polarity are Rho family small GTPase Cdc42 (Etienne-Manneville and Hall, 2001;Itoh et al, 2002), Par proteins, and atypical protein kinase (aPKC) (see (Ridley et al, 2003) for overview). Additional signals are provided by a gradient of phosphatidylinositol triphosphate (PIP3) (decreasing from front to rear), produced by the action of phosphoinositide-3 kinase (PI3K), and regulated by PTEN, a PIP3 phosphatase, which is located to the cell rear and controls the lower level of PIP3 at the trailing edge.…”
Section: Basic Principles Of Cell Migration Overall Structure Of the mentioning
confidence: 99%
“…The decrease of Rac activity seemed to be correlated to the knockdown levels of Crk-II. To confirm the decrease of Rac activation, we utilized FRET-based time-lapse analysis for monitoring the activity of Rac (Itoh et al, 2002). Positive signals were observed after serum stimulation in control cells, but not in Crk knockdown cells (Figure 3b and Supplementary data 5 and 6).…”
Section: Analysis Of Rac Activity By Pull-down Assay and Fret-based Tmentioning
confidence: 99%
“…FRET-based analysis of Rac activity pRachu-Rac-CAAX was transfected into MCAS cells, and 30 h later cells were cultured in DMEM with 2% FBS for 8 h. After 10% FBS stimulation, FRET-based analysis of Rac activity was performed following the methods established by Dr M Matsuda (Osaka University, Japan) (Itoh et al, 2002).…”
Section: Establishment Of Crk Knockdown Mcas Cellsmentioning
confidence: 99%